Multimodal Sensory Stimulation of the Masseter Muscle Reduced Precision but Not Accuracy of Jaw-Opening Movements - Wiesinger, Birgitta; Häggman-Henrikson, Birgitta; Eklund, Anton; Wänman, Anders; Hellström, Fredrik (Frontiers in Neuroscience, 2019)
A functional integration between the trigeminal and craniocervical sensorimotor systems has been demonstrated, with simultaneous jaw and head–neck movements during jaw opening–closing. We previously showed that pain induction in the masseter muscle increased the relative contribution of the neck component of integrated jaw–neck movements. Induced pain or manipulation of proprioception by vibration did not affect accuracy during a jaw-opening task in men. It is not known how multimodal sensory stimulation, with a combination of pain induction and vibration, affects jaw-opening accuracy and precision. The aim was to investigate how jaw–neck movements, and specifically accuracy and precision of jaw-opening, are affected during concomitant nociceptive and proprioceptive stimulation of the masseter muscle. Twenty-one healthy men performed jaw-opening to a target position, defined as 75% of individual maximum jaw-opening, during control (Ctr), vibration of masseter muscles (Vib), pain induction in the masseter (Pain), and concomitant vibration and pain induction in the masseter muscle (VibPain). Simultaneous jaw and head movements were recorded with an optoelectronic system and amplitudes calculated for each jaw opening–closing cycle. Accuracy of jaw movements was defined as the achievement of the target position. Precision of jaw movements was defined as the cycle-to-cycle variability from the mean of cycles 2–10 (coefficient of variation, CV). Differences between the trials were analyzed with Friedman’s test, Dunn’s test, and Benjamini-Hochberg correction. There were no significant differences between the trials for jaw movement amplitudes. For head movements, amplitudes for cycles 2–10 were larger during Pain compared to Ctr and Vib (both p=0.034), and larger during VibPain compared to Ctr (p=0.034) and Vib (p=0.035). There were no differences in accuracy of jaw movements between the trials. For precision of jaw movements, the cycle-to-cycle variability was larger during VibPain compared to Ctr (p=0.027) and Vib (p=0.018). For integrated jaw–neck motor strategy, there was a difference between pain and non-pain trials, but no differences between unimodal and multimodal stimulation trials. For achievement of jaw-opening to a target position, the results show no effect on accuracy, but a reduced precision of jaw movements during combined proprioceptive and nociceptive multimodal stimulation.